METODOLOGI TAFSIR MAUDHÛ’Î IMAM AL-SYÂFI’Î: Studi Tafsîr Al-Imâm Al-Syâfi’î Karya Ahmad Ibn Mushthafâ Al-Farrân - Muhammad Naji Bulloh Najib; Muhammad Sarbini Sarbini; Rahendra Maya Rahendra; Muhammad Fadilah Alfarisi Faris (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2024)
Muhammad ibn Idrîs Al-Syâfi’î or popularity known as Imam Al-Syâfi’î is an absolute independent mujtahid who masters various sciences which are the tools of ijtihad which become the basis for a mujtahid in carrying out ijtihad and formulating his own principles of legal research, including the science of interpretation even though he is not popular as a scholar who has works of interpretation. Now a work of commentary appears which collects various interpretations and interpretation of Imam Al-Syâfi’î on some of the letters and verses of the Al-Qur’an excavated from his various works. Namely the book of Tafsîr Al-Imâm Al-Syâfi’î which was collected by Ahmad ibn Mushthafâ Al-Farrân, which was identified as the first academic work to study the interpretation of Imam Al-Syâfi’î as a whole based on the systematics of the letters of the Al-Qur’an; derived from the dissertation work in the doctoral program. This article uses a qualitative research method of literature study which is descriptive-qualitative in nature with data collection techniques using library sources and documentary literature studies using descriptive-interpretative data analysis techniques with content analysis. In addition to introducing the book Tafsîr Al-Imâm Al-Syâfi’î by Ahmad ibn Mushthafâ Al-Farrân, this article also attempts to examine the maudhû’î interpretation methodology of Imam Al-Syâfi’î and his interpretation.